The new financial order : risk in the 21st century - Shiller, Robert J. (Princeton, NJ : Princeton University Press, 2003)
The book presents a fresh vision for hedging risk and securing our economic future.
Includes bibliographical references (p. 325-350) and index.
uaj 21/04/2015
Loan
Keywords: Risk management; Information technology